Media Coverage of Qatar’s Hosting of the World Cup 2022: (A Content Analysis of News Reports Posted on websites representing the neighboring Gulf States from 2016-2018) - Hessah Fahd Alhugbani (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
This study conducts a descriptive content analysis of media coverage from the Gulf States—Saudi Arabia, United Arab Emirates, Kuwait, and Oman—regarding Qatar's 2022 FIFA World Cup hosting. By analyzing sixty news articles retrieved from five popular news websites, Riyadh Daily, Saudi Gazette, The National, Kuwait Times, and Oman Observer, the study analyzed how these countries construct Qatar's capability to host the event in terms of economy, politics, socials, health, foreign relations, and environment from 2016 to 2018. This analysis uses the Chi-Square test and Krippendorff's Alpha to guarantee the validity and reliability of the research findings and convey an understanding of the media environment in the Gulf states and their effects on regional relations.